2002
DOI: 10.1093/genetics/162.4.1557
|View full text |Cite
|
Sign up to set email alerts
|

Defects in SPT16 or POB3 (yFACT) in Saccharomyces cerevisiae Cause Dependence on the Hir/Hpc Pathway: Polymerase Passage May Degrade Chromatin Structure

Abstract: Spt16/Cdc68, Pob3, and Nhp6 collaborate in vitro and in vivo as the yeast factor SPN, which is homologous to human FACT. SPN/FACT complexes mediate passage of polymerases through nucleosomes and are important for both transcription and replication. An spt16 mutation was found to be intolerable when combined with a mutation in any member of the set of functionally related genes HIR1, HIR2/SPT1, HIR3/HPC1, or HPC2. Mutations in POB3, but not in NHP6A/B, also display strong synthetic defects with hir/hpc mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(20 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In these processes, the nucleosome barrier needs to be temporarily disassembled to expose DNA for processing, and then be rapidly reassembled to protect the DNA and preserve the original epigenetic identity ( 3 , 4 ). Previous studies have found that FACT appears to function not only in destabilizing nucleosome to facilitate the progression of DNA and RNA polymerases on chromatins, but also in establishing and maintaining the genome-wide integrity of chromatin structure ( 9–15 ). In addition, recent in vitro structural and single-molecular investigations have revealed that FACT can tether both the (H3– ṇ H4) 2 tetramer and H2A–H2B dimer on DNA by its two subunits SPT16 and SSRP1, which functions distinctly but coordinately on the nucleosome disassembly and assembly ( 16–18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these processes, the nucleosome barrier needs to be temporarily disassembled to expose DNA for processing, and then be rapidly reassembled to protect the DNA and preserve the original epigenetic identity ( 3 , 4 ). Previous studies have found that FACT appears to function not only in destabilizing nucleosome to facilitate the progression of DNA and RNA polymerases on chromatins, but also in establishing and maintaining the genome-wide integrity of chromatin structure ( 9–15 ). In addition, recent in vitro structural and single-molecular investigations have revealed that FACT can tether both the (H3– ṇ H4) 2 tetramer and H2A–H2B dimer on DNA by its two subunits SPT16 and SSRP1, which functions distinctly but coordinately on the nucleosome disassembly and assembly ( 16–18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FACT ( FA cilitates C hromatin T ranscription) complex, initially identified as a chaperone of histone H2A–H2B dimer ( 5 ), is highly conserved among eukaryotes and essential for cell viability ( 6 , 7 ). Previous studies have found that FACT not only facilitates the progression of DNA and RNA polymerases on chromatin templates ( 5 , 8 ), but also functions to maintain the genome-wide integrity of chromatin ( 9–15 ). Recently, the in vitro structural and single-molecular investigations have revealed the functions of FACT by facilitating both the nucleosome disassembly and re-assembly ( 16–18 ).…”
Section: Introductionmentioning
confidence: 99%
“…FACT complex (a heterodimer of Spt16–Pob3 in yeast) has been reported to show genetic interaction with the Pol II elongation factors, physically associate and travel with Pol II during transcription elongation ( Squazzo et al 2002 ; Belotserkovskaya et al 2003 ; Mason and Struhl 2003 ; Saunders et al 2003 ; Schwabish and Struhl 2004 ) and influence transcription by Pol I and Pol II ( Formosa et al 2002 ; Mason and Struhl 2003 ; Biswas et al 2005 ; Birch et al 2009 ). FACT has been reported to influence transcription by Pol II at different steps via different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…20,[28][29][30][31] Biochemical studies in S. cerevisiae have shown that the complete Hir complex comprises 4 proteins (Hir1p, Hir2p, Hir3p and Hpc2p), which also show functional interactions with a wide range of chromatin associated complexes, such as the FACT, CAF-1, PAF1 and Swi2-Snf2 complexes. 19,21,[32][33][34][35][36] Additionally, genetic studies also imply that the Hir complex might function independently of Asf1 in maintenance of kinetochore chromatin structure. 32,33,36,37 Taken together the evidence suggests that the Hir complex and Asf1p are important generalized histone chaperones providing functional backup for a number of functionally specialized complexes involved in nucleosome deposition and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…19,21,[32][33][34][35][36] Additionally, genetic studies also imply that the Hir complex might function independently of Asf1 in maintenance of kinetochore chromatin structure. 32,33,36,37 Taken together the evidence suggests that the Hir complex and Asf1p are important generalized histone chaperones providing functional backup for a number of functionally specialized complexes involved in nucleosome deposition and remodeling.…”
Section: Introductionmentioning
confidence: 99%